2018
DOI: 10.1039/c8nj00394g
|View full text |Cite
|
Sign up to set email alerts
|

Structure of flower-like hierarchical CdS QDs/Bi/Bi2WO6 heterojunction with enhanced photocatalytic activity

Abstract: A CdS QDs/Bi/Bi2WO6 heterojunction was synthesized via a facile stepwise in situ reduction and deposition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The reason is that the establishment of heterojunction cannot only effectively broaden the range of light response and enhance the light absorption of catalyst but also achieve the effective separation of photo-generated carriers under the action of internal electric field and improve the catalytic activity [ 28 , 29 ]. Many Bi 2 WO 6 -based heterojunction photocatalysts, such as Bi 2 WO 6 /MoS 2 [ 30 ], Bi 2 WO 6 /Fe 2 O 3 [ 25 ], Bi 2 WO 6 /Bi 2 S 3 [ 31 ], CdS/Bi/Bi 2 WO 6 [ 32 ], meso-tetra (4-carboxyphenyl) porphyrin/rGO/Bi 2 WO 6 [ 33 ], and Co 3 O 4 /Ag/Bi 2 WO 6 [ 34 ], have been used to improve the performance of pure Bi 2 WO 6 . Huang et al successfully prepared a new flower-shaped AgBr/Bi 2 WO 6 catalyst, which showed good catalytic performance in the degradation of tetracycline (TC) under visible light (vis-light) irradiation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the establishment of heterojunction cannot only effectively broaden the range of light response and enhance the light absorption of catalyst but also achieve the effective separation of photo-generated carriers under the action of internal electric field and improve the catalytic activity [ 28 , 29 ]. Many Bi 2 WO 6 -based heterojunction photocatalysts, such as Bi 2 WO 6 /MoS 2 [ 30 ], Bi 2 WO 6 /Fe 2 O 3 [ 25 ], Bi 2 WO 6 /Bi 2 S 3 [ 31 ], CdS/Bi/Bi 2 WO 6 [ 32 ], meso-tetra (4-carboxyphenyl) porphyrin/rGO/Bi 2 WO 6 [ 33 ], and Co 3 O 4 /Ag/Bi 2 WO 6 [ 34 ], have been used to improve the performance of pure Bi 2 WO 6 . Huang et al successfully prepared a new flower-shaped AgBr/Bi 2 WO 6 catalyst, which showed good catalytic performance in the degradation of tetracycline (TC) under visible light (vis-light) irradiation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complementarily, several free noble metal materials have also been used as the electron mediator. For instance, g-C 3 N 4 /C@Bi 2 MoO 6 prepared by Chao Chai et al and CdS/CQDs/BiOCl with carbon acted as an electron mediator, , and CdS QDs/Bi/Bi 2 WO 6 by Jianjun Liu with a Bi bridge exhibited high photocatalytic activity in the application of aqueous pollutants. The superfine Bi NPs may provide a more economical alternative to the use of noble metals in such Z-scheme materials for its characters such as semimetal electrons conductivity and SPR similar to precious metal .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tiny Bi NPs produced in situ could well inhibit the leach and agglomeration, which is beneficial for the recycle stability . It has been reported that the plasmonic Bi NPs were used as electron transport media to construct the CdS/Bi/Bi 2 WO 6 and g-C 3 N 4 /Bi 2 MoO 6 /Bi heterojunction, exhibiting extraordinarily enhanced photocatalytic activity for the degradation of aqueous rhodamine B. , Thus, it gives us a clear hint that through an elaborate design, Bi NPs bridged Bi-based Z-scheme material may present an expectable ability in the application of the photocatalytic oxidation for indoor refractory VOCs with an easy operation and long-term usability.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many methods to synthesize CdS such as hydro-and solvothermal [9], template [10], and sol-gel [11]. Besides, flower-like [12], rod-like [13], and linear-like [14] CdS can be synthesized by these methods. An et al [15] have prepared pencil-like CdS nanorods and improved photocatalytic performance of CdS.…”
Section: Introductionmentioning
confidence: 99%